Pengaruh Pembelajaran Berdiferensiasi Catur Pramana Terhadap Motivasi Dan Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Kadek Sudiarta; I Made Ariasa Giri; Ni Nyoman Lisna Handayani (Jayapangus Press, 2025)
Low levels of learning motivation and critical thinking skills remain challenges in Hindu Religious Education at the elementary level. Students often show low engagement, procrastination, and weak analytical and argumentative abilities. This study examines the effect of differentiated learning oriented to the Catur Pramana learning cycle on the learning motivation and critical thinking skills of fifth-grade students in Cluster II, Buleleng District. The research employed a quantitative approach with a Posttest-Only Control Group Design. A total of 60 students were selected through simple random sampling. Data were collected using a motivation questionnaire and a critical thinking test, and analyzed with MANOVA using SPSS 20.0. The results revealed: (1) a significant difference in learning motivation between students taught with Catur Pramana-based differentiated learning and those taught conventionally (F = 63.915; p < 0.005); (2) a significant difference in critical thinking skills between the two groups (F = 15.398; p < 0.005); and (3) a simultaneous difference in motivation and critical thinking (Wilk’s Lambda = 11.936; p < 0.005). The experimental group achieved higher average scores, categorized as high, compared to the control group, which remained in the moderate category. In conclusion, integrating differentiated learning with the Catur Pramana learning cycle is proven effective in enhancing both learning motivation and critical thinking skills. These findings highlight the potential of Hindu local wisdom as a pedagogical innovation to strengthen the quality of elementary education.